Management Process in Incorporated Football Clubs: Istanbul Başakşehir Football Clubs Example - Gökalp Demir (Pakistan Journal of Medical & Health Sciences, 2022)
Sport sector has become a powerful industry formed by many stakeholders nowadays. Due to the fast progress of the communication age and the fact that sports competitions can meet people more easily, the number of spectators and participants of popular sports has increased and it has been instrumental in the recognition of new branches more easily. The increasing of the numbers has raised the number of athletes and sports clubs and the importance of the management activities of sports clubs. The sports sector, which has become an area where business people invest, has opened the way for football clubs to be managed like companies. Our study is to examine the management process of Başakşehir Football Club as a company. The club, which was previously owned by the municipality incorporated and renamed Istanbul Başakşehir Football Club later. The aim of the study is to see how these activities contribute to the club after the incorporation process. Qualitative research technique was used in the research. In this study, the concept of "case of study" was used for the research method. Semi-structured interview technique was used as data collection method. The data were subjected to content analysis. Sentences were chosen as the unit of analysis and presented with frequencies by transferring them to tables. The data obtained were analyzed with the content analysis method and three different themes (correct use of human resources, financial balance, long-term planning) emerged. These three themes have been the most important guide for the club, and Başakşehir Football Club has been protecting its success standard for a long time in this way.